2017
DOI: 10.1038/s41467-017-00498-4
|View full text |Cite
|
Sign up to set email alerts
|

Sirt6 deficiency exacerbates podocyte injury and proteinuria through targeting Notch signaling

Abstract: Podocyte injury is a major determinant of proteinuric kidney disease and the identification of potential therapeutic targets for preventing podocyte injury has clinical importance. Here, we show that histone deacetylase Sirt6 protects against podocyte injury through epigenetic regulation of Notch signaling. Sirt6 is downregulated in renal biopsies from patients with podocytopathies and its expression correlates with glomerular filtration rate. Podocyte-specific deletion of Sirt6 exacerbates podocyte injury and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
211
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 257 publications
(217 citation statements)
references
References 51 publications
5
211
0
1
Order By: Relevance
“…Currently, It is widely accepted that podocyte damage is not only associated with the degree of proteinuria, but also correlates with glomerulosclerosis development and renal function decline [2,3]. Podocyte damage is one of the early-stage events in many human kidney diseases, including minimal change disease (MCD), focal segmental glomerulosclerosis (FSGS), diabetic kidney disease (DKD), membranous nephropathy (MN), lupus nephritis (LN) and other CKDs [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, It is widely accepted that podocyte damage is not only associated with the degree of proteinuria, but also correlates with glomerulosclerosis development and renal function decline [2,3]. Podocyte damage is one of the early-stage events in many human kidney diseases, including minimal change disease (MCD), focal segmental glomerulosclerosis (FSGS), diabetic kidney disease (DKD), membranous nephropathy (MN), lupus nephritis (LN) and other CKDs [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The application of MS-275, a selective inhibitor of HDAC1 over HDAC3 and with no inhibitory activity towards HDAC8 effectively inhibits TGF-β signaling in renal interstitial fibroblasts. The treatment completely abolishes the expression of TGF-β receptor I and the phosphorylation of SMAD3, which suggests the efficient regulatory mechanism in several ways in fibrotic kidney diseases (33).…”
Section: Tgf-β Signaling Pathwaymentioning
confidence: 87%
“…Several studies have implied that the anomalous expression of nephrin, podocin and integrin a3b1 in podocytes would destroy the cells' normal structure and adhesive function, causing podocyte loss and apoptosis, which are closely related to the incidence of DN. Once podocyte damage occurs, the normal structure of foot processes is destroyed and the function is disordered, causing further podocyte injury and apoptosis, which are likely to lead to proteinuria, thus further promoting the development of renal functional injury and finally accelerating the DN progression 22 . In the present study, we found that the injection of STZ combined with a high-glucose/high-fat diet could significantly increase the FBG, promoting diabetic progression and further affecting renal function.…”
Section: Discussionmentioning
confidence: 99%